1994
DOI: 10.1007/bf02757541
|View full text |Cite
|
Sign up to set email alerts
|

YBa2SnO5·5, a novel ceramic substrate for YBCO and BiSCCO superconductors

Abstract: Al~tract. YBa2SnO~5 has been synthesized and sintered as single phase material for its use as substrate for both YBCO and BiSCCO superconductors. YBa2SnOs~ has a complex cubic perovskite (A2BB'O6) structure with the lattice constant a = 8.430 A. The dielectric constant and loss factor of YBa2SnOs. 5 are in a range suitable for its use as substrate for microwave applications. YBa2SnOs. 5 is found to be chemically compatible wRh both YBCO and BiSCCO superconductors. The thick film of YBCO screen printed on polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Yttrium can substitute for tin on the B site, leading to the solid-solution BaSn 1– x Y x O 3– x /2 , where the end-member BaSn 0.50 Y 0.50 O 2.75 again adopts a cubic perovskite structure (Figure a). In some of the previously obtained X-ray diffraction patterns weak reflections were, however, observed in addition to those expected for a cubic perovskite; these superstructure reflections were ascribed to Y 3+ and Sn 4+ ordering on the B site which results in an A 2 BB′O 6 superstructure (a double perovskite) involving a doubling of the ABO 3 unit cell. , The local structures occurring in these materials remain unclear since the intensities of the superlattice reflections are noticeably weaker than predicted for the fully ordered structure, indicating only partial Y/Sn ordering. Furthermore, no structural studies have been reported on materials with intermediate Y contents.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Yttrium can substitute for tin on the B site, leading to the solid-solution BaSn 1– x Y x O 3– x /2 , where the end-member BaSn 0.50 Y 0.50 O 2.75 again adopts a cubic perovskite structure (Figure a). In some of the previously obtained X-ray diffraction patterns weak reflections were, however, observed in addition to those expected for a cubic perovskite; these superstructure reflections were ascribed to Y 3+ and Sn 4+ ordering on the B site which results in an A 2 BB′O 6 superstructure (a double perovskite) involving a doubling of the ABO 3 unit cell. , The local structures occurring in these materials remain unclear since the intensities of the superlattice reflections are noticeably weaker than predicted for the fully ordered structure, indicating only partial Y/Sn ordering. Furthermore, no structural studies have been reported on materials with intermediate Y contents.…”
Section: Introductionmentioning
confidence: 91%
“…Although the present XRD measurements (Figure 3) do not reveal additional reflections of this type, they have been observed in previous studies, albeit with intensities significantly lower than would be predicted for full ordering. 4,5,36 For BaSn 0.60 Y 0.40 O 2.80 , while the Sn(OY Sn ′ ) 6 resonance again dominates (along with a shoulder attributed to environments such as Sn(OSn)(OY Sn ′ ) 5 ) the presence of a broad resonance at lower frequencies due to Y-poor environments suggests that the material comprises Sn-rich clusters within an overwhelmingly Y/Sn alternating ordered network. The transition from structural disorder to order from low to high Y doping levels appears to occur via a two-phase process: one phase being Y rich and ordered, and the second, Y poor and disordered.…”
mentioning
confidence: 99%
“…They have not so far been assessed for thick-film applications. Recently, Koshy and coworkers [21][22][23][24][25][26][27][28][29][30] have made significant advances in the development of materials for substrates, some of which are presented in table 2. Measurements of tan δ and dielectric constant were made in our laboratory in an oxygen-free copper cylindrical cavity with a vertically adjustable top plate.…”
Section: Materials For Substratesmentioning
confidence: 99%